2021
DOI: 10.1109/access.2021.3101471
|View full text |Cite
|
Sign up to set email alerts
|

Deep Flexible Transmitter Networks for Non-Intrusive Load Monitoring of Power Distribution Networks

Abstract: With the massive development of various new energy sources, the balance of supply and demand in the power grid faces a considerable challenge. A reliable way is to perform demand-side management on energies. For demand-side management, monitoring the load connected to power distribution networks is necessary. This paper proposes deep flexible transmitter networks to quickly monitor the load when the load is connected to power distribution networks. The proposed algorithm combines flexible transmitter networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The results indicated that using this technique the energy costs and load curtailment can be reduced. In [29], a NILM-based algorithm has been proposed for the monitoring of loads in the power distribution network. This technique consists of a neural network and improves accuracy by 5%.…”
Section: Studymentioning
confidence: 99%
“…The results indicated that using this technique the energy costs and load curtailment can be reduced. In [29], a NILM-based algorithm has been proposed for the monitoring of loads in the power distribution network. This technique consists of a neural network and improves accuracy by 5%.…”
Section: Studymentioning
confidence: 99%
“…According to the system requirements, each subsystem is designed independently, and they are connected with each other through a series of program interfaces to form a system. The communication program is responsible for the communication between the main Web server and the front-end computer, such as receiving telemetry signals, remote communication signals, alarm signals and coloring signals sent by the front-end computer, and sending remote control signals to the front-end computer by the main Web program [17]. Communication parameter description is used to describe parameter settings of serial communication port, card register information and network address port information.…”
Section: System Architecturementioning
confidence: 99%
“…Spite that linear state estimation is state-of-the-art, there are many other modern methods for state estimation in today's electric power systems. A state estimation by neural networks is investigated by [9], and [10] proposed a random forest algorithm of state estimation for appliances in office buildings. The Bagging classification algorithm and fuzzy analysis have good performances in state estimation and load monitoring, as reported by [11] and [12].…”
Section: Related Work and Nomenclaturementioning
confidence: 99%
“…From assumptions of the measurement errors, elements of U = (u i,j ) are independent, then the pdf of U is q(U) = i,j q i,j (u i,j ), U = (u i,j ) ∈ R (n+1)×(m+1) , (9) where q i,j (u) is the pdf of u i,j . From assumptions, q 0,i is a Gaussian pdf with known variance and its mean is 0.…”
Section: A Posterior Distribution and Map Estimatormentioning
confidence: 99%